Dry reforming of methane over Ni/KCC-1 catalyst for syngas production - Siti Nur Sabiha, Suhaimi; Syed Muhammad Wajahat58311223300, Ul Hasnain; Ahmad, Salam Farooqi; Herma Dina, Setiabudi; Syed Anuar, Faua’Ad Muhammad; Shahrul, Ismail; Bawadi, Abdullah (Association of American Publishers, 2023)
Dry reforming of methane (DRM) is a trendy topic of investigation as a means of reducing global warming. However, the adoption of DRM for a commercial purpose is still a question due to the deactivation and sintering of catalysts. The performance of the 5Ni/KCC-1 catalyst by using the ultrasonic-assisted impregnation method was examined in this study. The micro-emulsion method and ultrasonic-assisted impregnation method were used to prepare KCC- 1 support and 5Ni/KCC-1 catalyst respectively. The catalyst was characterized by N2 adsorptiondesorption and field emission scanning electron microscopy (FESEM) techniques. FESEM morphology shows that KCC-1 support experienced a well-defined fibrous morphology in a uniform microsphere which can promote high catalytic activity. The results show that the catalyst has optimum performance with higher reactant conversions and H2/CO ratio when operated at 850oC in a tubular furnace reactor as compared to 750oC.